Growth in infants, children and adolescents with unilateral and bilateral cerebral palsy - Ruiz Brunner, María de Las Mercedes (2022)
To compare growth patterns during infancy, childhood and adolescence in children with unilateral and bilateral cerebral palsy (CP) phenotype and to assess the association with gross motor impairment, dysphagia and gestational age. We retrospectively studied 389 children with CP from a single center population in Munich, Germany. 1536 measurements of height and weight were tabulated and z-scored from 6 to 180 months of age. Generalized linear mixed model were used to examine the association between growth, GMFCS, dysphagia and gestational age by CP phenotype. Children with unilateral CP tend to grow similarly to their typically developed peers. In the main effect model, bilateral CP phenotype was significantly associated with decreased mean z-scores for height (β [95% CI] − 0.953 [− 1.145, − 0.761], p < 0.001), weight (− 0.999 [− 1.176, − 0.807], p < 0.001) and BMI (β [95% CI] − 0.437 [− 0.799, − 0.075]), compared with unilateral CP phenotype. This association remained significant in the interaction models. The height-for-age z-scores, weight-for-age decreased z-scores and BMI-for-age z-scores of children with bilateral CP and GMFCS III–V or dysphagia decreased more significantly than those of children with unilateral CP. Preterm birth was not significantly associated with decreased growth in height, weight and BMI. Reduced growth in children with bilateral CP was strongly associated with moderate to severe impairment in gross motor function (GMFCS III–V) and dysphagia.